Effects of tillage practices on growth and yield of cassava (Manihot esculenta) and some soil properties in Ajibode, South-western Nigeria - AIYELARI, EMILOLORUN A; NDAEYO, NYAUDOH U; AGBOOLA, AKINOLA A (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted in 1994 and 1995 at Ibadan, Nigeria to evaluate the productivity of cassava (Manihot escuienta Crantz) and soil properties and dynamics under some tillage practices. Results revealed that tillage practices had no significant effect on sprouting percentage in 1994 but in 1995, heap treatment was significantly (P< 0.05) higher than others. Tillage had no marked effect on cassava height in both years while number of leaves only differed significantly from 8 months after planting with HP treatment being higher than others. Stem girth showed no marked differences among treatments in both years. Similarly. in both years, cassava fresh root yield and yield components were not significantly affected by tillage practices. The No-till slash and burn treatment showed signficantly higher soil bulk density at planting in both years than other treatments. Generally, soil chemical properties were not markedly affected by the tillage practices. The highest cost of production was observed under no-till slash and bum while ridge gave the highest economic returns. For successful growing of cassava under reduced tillage practices is practicable in this agro-ecological zone.